Biotagging, a genetically encoded toolkit in the zebrafish, reveals novel non-coding RNA players during neural crest and myocardium development - Chong, V (2017)
Complex multicellular organisms are composed of at least 200 cell types, which contain the same DNA "black box" of genetic information. It is the precise regime according to which they express their genes, exquisitely controlled by gene regulatory circuits, that defines their cellular identity, morphology and function. We have developed an in vivo biotinylation method that uses genetically encoded components in zebrafish, termed biotagging, for genome-wide regulatory analysis of defined embryonic cell populations. By labelling selected proteins in specific cell types, biotagging eliminates background inherent to analyses of complex embryonic environments via highly stringent biochemical procedures and targeting of specific interactions without the need for cell sorting. We utilised biotagging to characterise the in vivo translational landscape on polysomes as well as the transcriptional regulatory landscape in nuclei of migratory neural crest cells, which intermix with environing tissues during their migration. Our migratory neural crest translatome presented both known and novel players of the neural crest gene regulatory network. An in depth look into the active nuclear transcriptome uncovered a complex world of non-coding regulatory RNAs that potentially specify migratory neural crest identity and present evidence of active bidirectional transcription on regions of open chromatin that include putative cis-regulatory elements. Analysis of our transcribed cis-regulatory modules functionally links these elements to known genes that are key to migratory neural crest function and its derivatives. We also identified a novel cohort of circular RNAs enriched at regions of tandem duplicated genes. Last but not least, we recovered developmentally regulated long non-coding RNAs and transcribed transposable elements. To functionally dissect the biological roles of these factors, we have built two Ac/Ds-mediated in vivo toolkits for efficient screening of putative enhancers and for CRISPR/Cas9-based transcriptional modulation. Overall, our methods and findings present a comprehensive view of the active coding and non-coding landscapes of migratory neural crest on a genome-wide scale that refine the current regulatory architecture underlying neural crest identity.